LEGAL IMPACT ON SKINCARE BRAND OWNERS WHO VIOLATE BPOM REGULATIONS - Siregar, Aldi Nur; Saccai Srg, Mahesa Nurladuni; Khasanah, Nurul; Zahra, Syifa Az (LEX SOCIETAS: Journal of Law and Public Administration, 2025)
This research analyzes the legal impact on skincare brand owners who violate BPOM regulations. The focus of the research is on legal sanctions applied to skincare brand owners who do not meet product safety and quality standards. The results show that skincare brand owners who violate BPOM regulations can be subject to administrative, criminal, and civil sanctions. This research aims to provide a better understanding of the legal consequences for skincare brand owners who violate BPOM regulations. In addition, this research uses a normative juridical approach by examining applicable laws and regulations, such as Law Number 36 of 2009 concerning Health, Law Number 8 of 1999 concerning Consumer Protection, and BPOM regulations related to the circulation of cosmetic products. Secondary data from court decisions, regulations, and legal literature are also analyzed to strengthen the study. With this approach, the research is able to systematically map the forms of legal liability that must be faced by skincare brand owners who violate the provisions. The findings of this study emphasize the importance of skincare manufacturers' compliance with BPOM regulations as a form of protection for consumers and public health. Violations of regulations not only have implications for consumer losses, but can also damage brand reputation and cause financial losses due to lawsuits. Therefore